Urban Households Solid Waste Generated and Characteristics: The case of Shah Alam City Hall, Selangor. - Ali, Nor Eeda; Rahman, Norainah Abdul; Zainol, Halmi; Abdullah, Kamariah; Abdullah Saleh, Alia (Universitas Aisyiyah Yogyakarta, 2020)
The world's population growth, increasing urbanization and rising standards of living are some of the factors influencing waste generation in Malaysia. A self-administered questionnaire was used to collect primary data of the randomly selected 100 households. These households were provided with five (5)polythene bags to separate their daily wastes during the period of fourteen (14) days. The researcher visits each household in the evening to collect the polythene bags. A sample size, adequate to estimate the value with adequate precision was calculated from three residential neighborhoods (low, medium and high cost) The rate of waste generated from recyclable items are 45.51% (1,201.61 kg), followed by food wastes with 33.98% (897.18 kg) and non-recyclable items with 20.51% (541.54 kg). Therefore, the aim of this paper is to understand the waste generation and waste composition in relation to the willingness of the households and the objective are (i) to establish the nature of the waste generation and composition per/day; and (ii) to identify the current stakeholders involved in recycling material. The results clearly show that 96% of respondents are willing to participate in any program for waste minimization. This also indirectly indicates the lifestyle of the household.